The Effect of Manhwa on Reading Comprehension of Eighth-Grade Students - Widiyang Joko Wahyudi; Arin Inayah; Sutami Dwi Lestari (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
This research aims to find out whether there is any effect of using manhwa on the reading comprehension of eighth-grade students. This study is a quantitative research using pre-experimental design with a one-group pre-test and post-test. The sample consists of 18 students from class VIII, selected using purposive sampling. The data were collected through a multiple-choice reading test consisting of 20 items based on narrative texts. The data analysis was conducted using SPSS 26.0. The findings show that the students’ mean score increased from 51.39 in the pre-test to 86.67 in the post-test. The result of the t-test is higher than the t-table (6.889 > 2.109). Therefore, the researcher concludes that there is a significant effect of using manhwa as a learning medium on the reading comprehension of eighth-grade students at SMP Kosgoro Sragi.